Coherent control of high-harmonic generation using waveform-synthesized chirped laser fields - Wang, Xu; Jin, Cheng; Lin, Chii Dong (My University, 2014)
We show that waveform-synthesized chirped laser fields are efficient tools for coherent harmonic control. A single harmonic order, or two harmonic orders, can be selectively enhanced by using a two-color field allowing a moderate linear chirp for each color. Different harmonic orders within a wide spectral range can be selectively enhanced by adjusting the laser parameters. Our theory bridges two current harmonic control techniques, namely, single-color phase shaping and multicolor amplitude synthesis, and opens the door to new harmonic control possibilities.
Keywords: Harmonic control; Waveform-synthesized chirped laser fields